Figures 2-9 from: Zan ND, Sarbini A, Taha H, Tan IV, Azri A, Kahar R, Metali F, Ahmad N, Arai T (2020) Occurrence and ecological implication of a tropical anguillid eel, Anguilla marmorata, in Brunei Darussalam, Borneo Island. Zoologia 37: 1-7. https://doi.org/10.3897/zoologia.37.e39468 - Zan, Nur Dhabita; Sarbini, Ain; Taha, Hussein; Tan, Iy Vonne; Azri, Azie; Kahar, Rafhiah; Metali, Faizah; Ahmad, Norhayati; Arai, Takaomi (Zenodo, 2020)
Figures 2-9 Adult specimens (2, 3) and their teeth (4, 5) and gross morphologies (6, 7) and histological sections (8, 9) of the gonads of tropical anguillid eels, Anguilla marmorata, that were collected in Brunei Darussalam, Borneo Island: (2) BE-1, A. marmorata (962 mm in TL); (3) BE-2, A. marmorata (1352 mm in TL); (4) Narrow maxillary bands of teeth of BE-1; (5) Narrow maxillary bands of teeth of BE-2. The gonadal histology of Stage III (8; BE-1) showed oocytes with oil droplets mid-vitellogenic oocytes in the early maturation stage. The gonadal histology of Stage V (9; BE-2) showed mid-vitellogenic oocytes (arrows) in the final preparation for spawning. Gross morphologies of the gonads (6, 7) are indicated by arrows. Scale bars: 8, 9 = 50 µm.